# Which of the following are solutions to the equation (x-a)(x-b)=0?a) x= -a and a= -b b) x=a and x=b c) x=ab d) x= (-a)(-b) e) x= 2a=2b

*print*Print*list*Cite

Expert Answers

jgeertz | Certified Educator

(x-a) (x-b) =0

If either (x-a)=0 or (x-b)=0 then the entire expression is equal to 0.

Set the first factor equal to 0 and solve.

(x-a) =0

x=a

Set the next factor equal to 0 and solve.

(x-b) =0

x=b

**The solution is all values that make (x-a)(x-b) =0 true.**

**x= a, b **

**which in your problem is choice b) x=a, x=b**